2021
DOI: 10.1186/s13578-020-00526-9
|View full text |Cite|
|
Sign up to set email alerts
|

Mettl14-mediated m6A modification modulates neuron apoptosis during the repair of spinal cord injury by regulating the transformation from pri‐mir‐375 to miR-375

Abstract: Background Spinal cord injury (SCI) is a disabling disorder, resulting in neurological impairments. This study investigated the mechanism of methyltransferase-like 14 (Mettl14) on apoptosis of spinal cord neurons during SCI repair by mediating pri-microRNA (miR) dependent N6-methyladenosine (m6A) methylation. Methods The m6A content in total RNA and Mettl14 levels in spinal cord tissues of SCI rats were detected. Mettl14 expression was intervened i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…m6A2Target database predicted that METTL14 might work on EEF1A2 and regulate its downstream methylation (Table 1 ). METTL14 and m6A were elevated in spinal cord tissues in SCI, and impaired motor function was restored and neuronal apoptosis was decreased after silencing METTL14 [ 22 ]. SRAMP database predicted that EEF1A2 might be modified by m6A methylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…m6A2Target database predicted that METTL14 might work on EEF1A2 and regulate its downstream methylation (Table 1 ). METTL14 and m6A were elevated in spinal cord tissues in SCI, and impaired motor function was restored and neuronal apoptosis was decreased after silencing METTL14 [ 22 ]. SRAMP database predicted that EEF1A2 might be modified by m6A methylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Laminectomy (3 mm) was performed from the caudal end of the T10 vertebra to the caudal end of the T11 vertebra under a dissection stereomicroscope. Infinite Horizons impactor (Infinite Horizons, L.L.C., Lexington, KY, USA) was utilized to induce contusion SCI at the force of 60 kdyn/cm [ 2 , 22 ]. The incision was sutured, followed by intramuscular injection of 20000 units of penicillin once a day for three days.…”
Section: Methodsmentioning
confidence: 99%
“…Recent researches have demonstrated that dysregulation of METTL14 is tightly relative to the phenotypes involved in the malignant development of various cancer, including proliferation [88][89][90], metastasis [91][92][93][94][95][96], apoptosis [97][98][99][100][101], drug resistance [102][103][104][105], cancer stem cell like characteristic [106,107], immunotherapy [21,108,109], chronic inflammation [110] and glycolipid metabolism (Fig. 2) [95].…”
Section: The Function Role Of Mettl14 In Gastrointestinal Cancermentioning
confidence: 99%
“…Therefore, the study of ferroptosis-related genes and proteins will be an important strategy to attenuate neuronal and oligodendrocyte injury and promote the recovery of neurological function after SCI. Our previous work showed that Mettl14-mediated m6A modification inhibited RASD1 and induced the apoptosis of spinal cord neurons in SCI by promoting the transformation of pri-miR-375 to mature miR-375 ( 123 ). However, it is still unclear of the iconic molecules of ferroptosis yet, the study of ferroptosis mechanism is still not deep enough, and the role of ferroptosis in SCI is still in the mist, the studies with patient and clinical proximity are relatively rare, which are the urgent issues in this field.…”
Section: Ferroptosis In Scimentioning
confidence: 99%